FLUOROQUINOLONE RESISTANCE PATTERN AMONG THE PATHOGENS CAUSING URINARY TRACT INFECTION IN A TERTIARY CARE HOSPITAL IN KANCHIPURAM DISTRICT, TAMIL NADU, INDIA - BANUKUMAR, Shanthi; I, Kannan; Rg, Sukumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The aim is to study the fluoroquinolone resistance pattern among the pathogens causing urinary tract infection (UTI). Methods: This study was done during January to July 2016 in Tagore Medical College including both hospitalized and out patients. During this 7-month study, around 2695 urine samples were analyzed for the evidence of UTI. 718 samples were culture positive. 366 samples showed fluoroquinolones resistance (50.9%). They were screened for all fluoroquinolone drugs by doing antimicrobial susceptibility testing by Kirby-Bauer disc diffusion method as per the Clinical and Laboratory Standards Institute CLSI guidelines. Results: The resistance pattern of different isolates to norfloxacin is Klebsiella pneumoniae - 20%, Escherichia coli - 51.4%, Enterococci - 11.1%, Proteus mirabilis - 50%, and Staphylococcus saprophyticus - 37.5%; For nalidixic acid is K pneumoniae - 25%, E. coli - 6.8%, Pseudomonas aeruginosa - 71.4%, Enterococci - 11.1%, P. mirabilis - 25%, and S. saprophyticus - 25%; For ciprofloxacin is K. pneumoniae - 5%, E. coli - 5.4%, P. mirabilis - 25%, and S. saprophyticus - 25%; and For ofloxacin is K. pneumoniae - 10%, E. coli - 5.4%, Enterococci 11.1%, and S. saprophyticus 62.5%. Conclusion: Due to increasing resistance to fluoroquinolones in many hospitals and to make the developing resistance rates under control, empirical usage of it is either abandoned or should be restricted.